«TO UNDERSTAND THE LOGIC OF MISFORTUNE»: TACTICS AND STRATEGIES OF HUMAN AND PROFESSIONAL SURVIVAL IN THE YEARS OF REVOLUTIONARY CHANGE (BASED ON WRITERS’ DIARIES) (Филологический класс, 2018)
The article deals with the problem of self-determination and understanding of one’s position and professional identity in the years of revolutionary change in auto-documentary texts of writers. The research material includes «Diaries» by K. Chukovsky, «Notebooks» by L. Ginzburg and «The Diary» by L. Shaporina. It is a diary that is a means of correlation, of including oneself in the historical time. The article focuses on the strategies and tactics of the writers’ adaptation to the new political and cultural situation. The article argues that the writers’ positions were not limited to the dilemma of servile obedience or heroic resistance to the regime. Egodocuments (diaries, notebooks) demonstrate the process and dynamics of choice in the situation when one-and-only choice is impossible. In his diary, K. Chukovsky chooses the role of an observer. Like many other people, he had to “put on a mask”, but hardly perceivable engagement in the Soviet reality also took place. The position of L. Ginzburg is ridden with inner conflict: she accepts new reality as a given fact but realizes the futility of former writer’s aims. The writer’s task under such conditions is not to lose professionalism. Then the article passes on to the analysis of the diary of a painter and theatrical worker L. Shaporina. The revolutionary overthrow inspired in her a feeling of creative inspiration, but the cultural collapse was becoming more and more evident. L. Shaporina sees her mission in the activity aimed at preservation of cultural succession in a new, unfavorable situation. The article concludes about the gradual distancing of the authors under study from the image a «correct» Soviet writer and about the growing feeling of personal misfortune. Still, it is these ego-documents that are on high demand nowadays.